Hull wake measurement in steady drift using a boroscopic stereo-PIV system. (May 2019) - Capone, A; Alves Pereira, F; Maiocchi, A; Camussi, R; Di Felice, F
Abstract: Particle Image Velocimetry measurements in towing tanks usually require ad-hoc solutions to address the need to protect electronic equipment from water. Pioneering works in this field rely upon fully underwater probe systems to address this issue, as in [1]. In this work we present an approach based on the use of endoscopic equipment (boroscopes) to carry out towing-tank Stereo PIV (SPIV) measurements of the hull wake of a ship model in steady drift. A boroscopic SPIV system provides increased flexibility thanks to the absence of water-proof camera casings. The only underwater components of the presented apparatus are the boroscope tubes and the light-sheet forming device, which are not critical in terms of water protection. The major drawbacks are the reduced light-collecting efficiency of the boroscope devices as well as the geometric deformations and aberrations due to the short focal length, which must be specifically addressed with adequate algorithms. The boroscope-based SPIV system presented in this work features three cameras for redundancy and to increase measurement accuracy. We present the results of towing-tank testing of the hull wake of a twin-screw model at Froude number Fr = 0.24 in straight-ahead and steady drift conditions.